Adsorção de tiametoxam em caldo de cana-de-açúcar (Saccharum spp) por carvão ativado nanomodificado e determinação por Cromatografia Líquida de Alta Eficiência (CLAE-DAD) - Freitas, Driélle Aparecida de (2019)
The cultivation of sugarcane is one of the oldest in human civilization. In Brazil the species Saccharum officinarum is of greater importance for the sugar-alcohol sector due to its high levels of sucrose. Over time, several factors and conditions allowed Brazil to be one of the largest producers of this cultivar. However, in order to guarantee high productivity, high levels of pesticides are applied in this crop, among which the neonicotinoid and systemic insecticide thiamethoxam (TMX) stands out. Systemic insecticides applied in crops are of great concern due to the possibility of the consumption of their derivatives by humans and animals. Therefore, considering the sugarcane juice a food matrix and the risks that TMX residues can offer, the objective of this work was to develop and validate a chromatographic method for quantification of this pesticide, as well as to evaluate its removal from aqueous and sugarcane juice media by a magnetic activated charcoal nanocomposite (AC-NP). The synthesis of ACNP was performed by the coprecipitation method, and the composite was characterized by XDR, FTIR, and SEM. After TMX adsorption assays, the pesticide was quantified by High Performance Liquid Chromatography coupled with a diode array detector (HPLCDAD) at 254 nm. The chromatographic operating conditions were: mobile phase acetonitrile:water (30:70) at 1.0 mL min-1 flow rate; C18 column; sample injection volume 20 μL; and analysis time of 6 min. The main parameters of the validation presented satisfactory results, and the selectivity of the method for TMX was observed in both water and sugarcane media, with limits of detection and quantification of 0.057 and 0.17 mg L1, respectively, and 4.6 min retention time. The matrix effect was not observed and r2 ranged from 0.9958 to 0.9985. Recovery tests presented results between 91 and 103%, and the coefficient of variation range was 1.9 – 4.3%. The nanomodification process was satisfactory and the characterization of AC-NP allowed to observe the effective impregnation of the magnetite. The TMX adsorption kinetics in sugarcane juice by ACNP was a pseudo-second order type, with r2 of 0.9999, indicating a chemical adsorption process. The experimental sorption capacity (SC) for both TMX (standard) and TMX-FP (formulated product) were 13.3 and 65.7 mg g-1, respectively, and Freundlich and SIPS isothermal models best fit the TMX data (r2 = 0.9740 and 0.9716), while TMX-FP data were adjusted to Langmuir and SIPS (r2 0.9941 and 0.9943). Therefore, it was possible to conclude that the chromatographic method proposed for the quantification of TMX and TMX-FP in aqueous and sugarcane juice media was highly satisfactory, and validated for its main parameters. The efficiency of AC-NP in the sorption of this analyte was confirmed by the excellent values of SC and kinetics, indicating its favorable use in the removal of TMX from complex matrices.